HUBUNGAN FAKTOR INDIVIDU TERHADAP PENINGKATAN OMZET PADA TOKO BANGUNAN SINAR ABADI SORONG - ADELMA SUSANA LAISINA, (Journal of Management and Accounting (JMA), 2026)
This study aims to determine how the relationship of individual factors to the increase in turnover at Sinar Abadi Stores, Sorong. This study uses a quantitative approach with data analysis techniques are simple linear regression analysis, classical assumption test and analysis of the coefficient of determination. Thus the data obtained from the analysis that the relationship of individual factors to the increase in turnover is very influential. This is proven based on the results of the linearity test on individual factors, a significance value of 0.000 is obtained. The significance value obtained is <0.05. Based on the test criteria with probability with a significance level of 0.05 (5%) it can be said that the two variables between the variables x and y have a linear relationship.